Recent Publications (Quarterly Journal of Economics, 1955)
Recent Publications Get access The Quarterly Journal of Economics, Volume 69, Issue 3, August 1955, Pages 480–483, https://doi.org/10.1093/qje/69.3.480 Published: 01 August 1955